Development of Grid-Connected Photovoltaic System Design Tool for Residential Building - Abdullah, Mohd Noor; Yong, Her Ming (Evolution in Electrical and Electronic Engineering, 2021)
This work presents the development and simulation of the design tool for a grid-connected photovoltaic system for residential buildings. The main difference between the grid-connected photovoltaic (GCPV) system and a standalone photovoltaic (SPV) system is GCPV system is with the grid while the SPV system is without connecting the system to the grid. The grid-connected photovoltaic system sizing calculation is very complex. It has made the project engineer spend a lot of time doing the calculation manually. Thus, the GCPV Design Tool played a vital role in simplifying the process of getting the result for the GCPV system sizing. Even though there are many kinds of PV system simulation software in the market, that software is sold at a very high price. The proposed design tool has been developed by using Microsoft Excel Visual Basic. The proposed design tool can be used to identify the sizing of the GCPV system and conduct the performance, environmental and economic analysis on the recommended GCPV system. The case study has been conducted by using both the proposed design tool and PVsyst to design a GCPV system for the user at Johor Bahru. The result of PV panel and inverter sizing obtained by the proposed design tool is similar to PVsyst software.